The rise and fall of the age of psychopharmacology - Shorter, Edward (New York, NY : Oxford University Press, 2021)
Medicine generally is about the story of progress, but psychiatry's story is that of failure in diagnosis, in therapeutics, and in the ability to deliver science-based care to suffering individuals.'In The Rise and Fall of the Age of Psychopharmacology', esteemed historian Edward Shorter proposes that the recent history of psychiatry is that of a failed scientific discipline of medicine.
Also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 2, 2021).
Keywords: Psychopharmacology; Psychopharmacology -- History; Psychotropic drugs